Using Steganography & Cryptography to Hide Data in EXE Files - P. Shetty, Nisha; Ranjan, Nikhil (International Journal of Engineering and Technology, 2018)
The most common term we hear when talking about data security is Cryptography; it comprises of practices and study of techniques for secure communication from one party to another without compromising private data that is to be shared between them. The objective of cryptography in simple words is to hide the plain text/data by modifying it into a cypher text/data such that no third party can read it easily. Another term less commonly known is Steganography; it is the process of hiding/encoding a secret message within an ordinary or dummy data file and the simple extraction of it at its destination.Our project aims to combine the best features of the two worlds. The raw data is first compressed, and then split into bytes for encryption via AES. Once encryption is done the encrypted data is hidden behind an exe file. Additionally a SHA-256 hash of the compressed original data is also included to evaluate file integrity.Â Â Â